(untitled) (Ustozlar uchun, 2026)
This thesis explores the emerging landscape of future employment and provides a comprehensive analysis of the jobs that are expected to exist by the year 2050. Rapid advancements in artificial intelligence, robotics, biotechnology, nanotechnology, renewable energy, and space exploration are reshaping the global labor market. As automation takes over routine and repetitive tasks, new professions will arise that require creativity, digital literacy, emotional intelligence, advanced problem-solving, and interdisciplinary knowledge. The study examines predicted career fields such as AI-ethics specialists, human–machine interaction designers, robotics coordinators, climate adaptation analysts, genetic modification consultants, digital wellness coaches, virtual environment architects, renewable-energy technicians, and interplanetary travel personnel.